Survivable green traffic engineering with shared protection. Issue 1 (14th November 2016) - Addis, Bernardetta; Carello, Giuliana; Mattia, Sara
Abstract : This article focuses on the problem of minimizing the energy consumption in a resilient telecommunications network. For each demand, an edge‐disjoint pair of paths (primary and backup) must be provided and the shared protection scheme is used. The energy consumption is due only to edges used in the no‐fault scenario, but both primary and backup paths contribute to capacity consumption. We propose a projected formulation for the problem and show its effectiveness by comparing it with the complete formulation. We propose valid inequalities for both formulations. We evaluate the performances of the proposed formulations and valid inequalities through computational tests. Furthermore, we investigate the relationship between the shared and the dedicated protection version of the problem. © 2016 Wiley Periodicals, Inc. NETWORKS, Vol. 69(1), 6–22 2017